2009
DOI: 10.1128/jcm.00397-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of SCC mec Type in Outcome of Staphylococcus aureus Bacteremia in a Single Medical Center

Abstract: Staphylococcus aureus virulence factors may determine infection presentation. Whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…Although some studies have shown that SCCmec II is associated with a higher mortality rate compared to the other SCCmec types [5], we have previously shown no significant difference between the type of SCCmec and clinical cure and mortality among patients with MRSA cSSTIs [6]. This has also been confirmed by other studies [7] [8].…”
Section: Discussionsupporting
confidence: 79%
“…Although some studies have shown that SCCmec II is associated with a higher mortality rate compared to the other SCCmec types [5], we have previously shown no significant difference between the type of SCCmec and clinical cure and mortality among patients with MRSA cSSTIs [6]. This has also been confirmed by other studies [7] [8].…”
Section: Discussionsupporting
confidence: 79%
“…All PCR amplicons in our multiplex platform are Յ174 bp long (Table 1), thereby contributing directly to increased amplification efficiency and sensitivity of detection using minimal reaction volumes, as well as facilitating analysis of low-quality/fragmented DNA. The sensitivity afforded by our method may also allow for SCCmec typing directly from blood cultures (38), which is of potential interest in light of recent reports describing differences in clinical outcome between S. aureus bacteremias associated with particular SCCmec types (19).…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate from SAB varies depending on the primary focus of infection, with the highest mortality rates occurring in patients with primary bacteremic pulmonary infections (33,39,41,96,206,296,301) and infective endocarditis (IE) (77,168,237,296,301).…”
Section: Host-pathogen Interactions Principal Diagnosis and Source Ofmentioning
confidence: 99%
“…These comorbidities include the presence of alcoholism (131), immunosuppression (131), cirrhosis (133,134,138,140), congestive cardiac failure (171), malignancy (33,77,133,134,140,308,309), chronic renal failure requiring hemodialysis (77,131,134,184), and the presence of multiple comorbidities (14).…”
Section: Presence Of Comorbiditiesmentioning
confidence: 99%